2021
DOI: 10.26508/lsa.202000935
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer is marked by complement-high blood monocytes and tumor-associated macrophages

Abstract: Pancreatic ductal adenocarcinoma (PDA) is accompanied by reprogramming of the local microenvironment, but changes at distal sites are poorly understood. We implanted biomaterial scaffolds, which act as an artificial premetastatic niche, into immunocompetent tumor-bearing and control mice, and identified a unique tumor-specific gene expression signature that includes high expression of C1qa, C1qb, Trem2, and Chil3. Single-cell RNA sequencing mapped these genes to two distinct macrophage populations in the scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 54 publications
5
62
0
Order By: Relevance
“…Additionally, we observed downregulation of the complement genes C1qa, C1qb, C1qc and the transcription factor Trem2, which together define TAMs in several malignancies (45). Our group has also recently described a population of C1qa + C1qb + Trem2 + macrophages enriched in human and mouse pancreatic cancer both at the primary tumor and in liver metastases (46). These findings are consistent with TAM gene expression markers being activated in macrophages during the onset of neoplasia.…”
Section: Extrinsic Signaling From Kras* Transformed Cells Drives Myeloid Polarizationsupporting
confidence: 86%
“…Additionally, we observed downregulation of the complement genes C1qa, C1qb, C1qc and the transcription factor Trem2, which together define TAMs in several malignancies (45). Our group has also recently described a population of C1qa + C1qb + Trem2 + macrophages enriched in human and mouse pancreatic cancer both at the primary tumor and in liver metastases (46). These findings are consistent with TAM gene expression markers being activated in macrophages during the onset of neoplasia.…”
Section: Extrinsic Signaling From Kras* Transformed Cells Drives Myeloid Polarizationsupporting
confidence: 86%
“…There are still different types of cancer (e.g., pancreatic cancer) that have not been analyzed in the context of NUCB2 expression. Pancreatic ductal adenocarcinoma (PDA) is a lethal malignancy with a dismal 5-year survival rate of only 10%, making it one of the most aggressive cancers worldwide [ 79 ]. Recent studies succeeded in isolating different pancreatic cell types from mouse and human pancreas [ 80 , 81 ].…”
Section: Nucb2 In Cancer Proliferation Apoptosis Migration and Invasionmentioning
confidence: 99%
“…Consistently, C1QA and C1QB were confirmed to be drivers of alternatively activated macrophage polarization in a LPS-induced inflammation model (47). Samantha et al (48) reported that macrophages express high levels of C1QA and C1QB in both primary tumor and metastases. C3AR1 as a receptor of the complement effector C3a, is important in mediating the downstream signal transduction of the complement activation.…”
Section: Discussionmentioning
confidence: 73%
“…Samantha et al. ( 48 ) reported that macrophages express high levels of C1QA and C1QB in both primary tumor and metastases. C3AR1 as a receptor of the complement effector C3a, is important in mediating the downstream signal transduction of the complement activation.…”
Section: Discussionmentioning
confidence: 99%